Kesatuan Liturgis dan Teologis Perayaan Trihari Suci - Stenly Vianny Pondaag; Checilia Cindy Jenifer Alida Pinedendi (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
This paper aims to explore the true meaning of the Mysterium Paschale, namely Christ's passion, death, and resurrection, based on the liturgical celebration of the Sacred Triduum where the Church solemnly celebrates the greatest mysteries of redemption, namely the special celebrations of the memorial of the Lord, crucified, buried, and risen. This paper is designed as a hermeneutic qualitative research. The theological examination leads the author to some critical findings. First, the Sacred Triduum should be seen as one liturgical celebration that lasts three days. The Sacred Triduum shows an unseparated sequence of liturgical celebrations. Then, the Sacred Triduum regarded as one liturgical celebration reveals in turn a unified theological meaning, namely Mysterium Paschale which consists of the mystery of the passion, death, and resurrection of Christ. By looking at the unity of the celebration of the Sacred Paschal Triduum and of its theological meaning, it is recommended that the faithful may prepare for the celebration thoroughly and be able to participate in the celebration of the Sacred Paschal Triduum as a whole so that they can experience the Easter Mystery as the culmination of the history of our redemption.